Community Assistance In Improving Understanding Of Religious Moderation Based On Family Maslahah In Jambewungu Village Wringin District Bondowoso - Shohibul Ulum; Lucky Damara Yusuf (Values: Jurnal Kajian Islam Multidisiplin, 2025)
In preparing the planning of community guidance and development activities in improving the Human Resources of the Maslahah Family in Jambewungu Village, Wringin District. The purpose of this community service is to implement and develop the Tri Dharma of Higher Education synergistically. The method we obtained in this service activity is the creation of transformative learning, an important process that determines changes in a person's knowledge, attitudes, skills and behavior. Activities that will be carried out in mentoring in the fields of religion, education and socio-culture.